2016
DOI: 10.1080/02687038.2016.1225274
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Communicative Participation Item Bank (CPIB) for use with people with aphasia: an analysis of differential item function (DIF)

Abstract: Background: The term ‘communicative participation’ refers to participation in the communication aspects of life roles at home, at work, and in social and leisure situations. Participation in life roles is a key element in biopsychosocial frameworks of health such as the World Health Organization’s (WHO) International Classification of Functioning, Disability and Health (ICF), and the Aphasia Framework for Outcomes Measurement (AFROM). The Communicative Participation Item Bank (CPIB) was developed as a patient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 40 publications
0
34
1
Order By: Relevance
“…All responses to items on the outcome measures included in the quantitative studies needed to be from the person with the communication disorder (i.e., patient-reported). Responses generated by proxies such as clinicians or family members may yield different results from the individual with the communication disorder (Baylor et al 2017, Cruice et al 2005. As a result, studies that solely included responses from proxy raters were excluded.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…All responses to items on the outcome measures included in the quantitative studies needed to be from the person with the communication disorder (i.e., patient-reported). Responses generated by proxies such as clinicians or family members may yield different results from the individual with the communication disorder (Baylor et al 2017, Cruice et al 2005. As a result, studies that solely included responses from proxy raters were excluded.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…In addition to perceived social support, factors include disorder severity, other environmental influences, and personal factors (e.g., coping responses). All of these variables have been found to affect communication outcomes in different populations, and all need further study (Baylor et al 2017, Baylor et al 2010, Hilari et al 2012, McAuliffe et al 2016, Yorkston et al 2001.…”
Section: Future Directions and Limitationsmentioning
confidence: 99%
“…The CPIB was developed using IRT, and the analysis to evaluate item parameter differences between populations in IRT is an analysis of differential item functioning (DIF; Choi, Gibbons, & Crane, 2011). Prior studies with the CPIB have revealed no meaningful DIF across groups with different speech and language disorders (e.g., Baylor et al, 2016Baylor et al, , 2013 as well as between two different countries (Baylor et al, 2014). However, given the patterns observed in the descriptive feedback in this study, it is possible that DIF may be observed between the groups with speech and language disorders versus individuals with hearing loss, particularly on the items that participants with hearing loss found less relevant to their experiences.…”
Section: Discussionmentioning
confidence: 99%
“…One 10-item short form is currently available for clinical and research use (Baylor et al, 2013). That short form has been validated for adults with speech and language disorders (Baylor et al, 2016(Baylor et al, , 2013. Future goals for CPIB development include computerized adaptive testing (Cook, O'Malley, & Roddey, 2005).…”
mentioning
confidence: 99%
“…As of this writing, there are few validated measures dedicated to communicative participation, which may be related to several challenges in developing these instruments including agreeing on the definition and scope of the construct of 'participation,' as well as the rigorous process for developing measures demanded in the current state of measurement science (Brandenburg, Worrall, Rodriguez, & Bagraith, 2015;Darling-White, 2017). Published PROs for adults include the Communicative Participation Item Bank (CPIB) that captures the extent to which the individual feels he or she is experiencing restrictions in daily conversational situations (Baylor et al, 2014;Baylor et al, 2017;Baylor et al, 2013;C. Miller, Baylor, Birch, & Yorkston, 2017).…”
Section: Measuring Communicative Participationmentioning
confidence: 99%